Haplotype and ribotype diversity of Saxifraga cuneifolia s. l. (Saxifragaceae). Issue 4 (19th May 2019) - Sanna, Mauro; Cires, Eduardo; Pérez-Haase, Aaron; Fernández Prieto, José Antonio
Abstract : Saxifraga cuneifolia L. (sect. Gymnopera, Saxifragaceae) is a plant distributed in the main mountain ranges of southern Europe, from the eastern Pyrenees to the eastern Carpathian. Currently, two subspecies are recognized based on morphological characteristics: S. cuneifolia subsp. cuneifolia grows in the Maritime Alps and North Apennines and S. cuneifolia subsp. robusta is located in the remaining area of distribution. A more delicate form and a smaller number of flowers in S. cuneifolia subsp. cuneifolia are the morphological characteristics that differentiate this subspecies from the widespread S. cuneifolia subsp. robusta . To explore the genetic diversity and the subspecific geographic patterns of S. cuneifolia s. l. we conducted a molecular study of nuclear and plastid sequences. Samples of S . cuneifolia s. l. have been analysed throughout the distribution area of this species. Our results, based on nuclear (ITS) and plastid ( rbcL, trnL–F, and psbA–trnH ) markers, showed a genetic characterization of both subspecies presenting discriminant haplotypes and ribotypes that confirm the current subspecific systematics.